2013
DOI: 10.1177/1934578x1300801014
|View full text |Cite
|
Sign up to set email alerts
|

Monanchomycalin C, a New Pentacyclic Guanidine Alkaloid from the Far-Eastern Marine Sponge Monanchora Pulchra

Abstract: A new pentacyclic guanidine alkaloid, monanchomycalin C (1), along with the earlier known ptilomycalin A (2), were isolated from the Far-Eastern marine sponge Monanchora pulchra. The structure of 1 was elucidated using 1D and 2D NMR spectroscopic and mass spectrometric data. Compounds 1 and 2 exhibited cytotoxic activities against human breast cancer MDA-MB-231 cells with IC 50 values of 8.2 µM and 4.3 µM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 38 publications
2
45
0
2
Order By: Relevance
“…It was suggested that the C-37 atom is located in an acyclic residue, but not in a morpholinone ring, in contrast with other known monanchocidins. Analysis of the NMR data (Table 1) and taking into account that the molecular weight of normonanchocidin A (1) is less than that of monanchocidin A by 101 amu, we concluded that its "anchor" part is a derivative of 1,3-diaminopropane (substructure "a", Figure 1), which has never before been found in Far-Eastern and tropical pentacyclic guanidine alkaloids [1][2][3][4][10][11][12][13][14][15][16][17][18][19]. Further analysis of the 1 H NMR data of 1 revealed the presence of branching in the chain fragment, indicated by the triplet for CH 3 -43 at δ H 0.84, similarly to that found earlier in the spectrum of monanchocidin A [1].…”
mentioning
confidence: 80%
“…It was suggested that the C-37 atom is located in an acyclic residue, but not in a morpholinone ring, in contrast with other known monanchocidins. Analysis of the NMR data (Table 1) and taking into account that the molecular weight of normonanchocidin A (1) is less than that of monanchocidin A by 101 amu, we concluded that its "anchor" part is a derivative of 1,3-diaminopropane (substructure "a", Figure 1), which has never before been found in Far-Eastern and tropical pentacyclic guanidine alkaloids [1][2][3][4][10][11][12][13][14][15][16][17][18][19]. Further analysis of the 1 H NMR data of 1 revealed the presence of branching in the chain fragment, indicated by the triplet for CH 3 -43 at δ H 0.84, similarly to that found earlier in the spectrum of monanchocidin A [1].…”
mentioning
confidence: 80%
“…Fluorescent assays were performed as described in [6]. The alkaloid’s solutions of desired concentration were obtained by serial dilution of water stock solutions (10 mg/mL) in calcium assay buffer (10 mM HEPES/HBSS, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years it has been shown that the far-eastern marine sponge Monanchora pulchra is also a rich source of novel pentacyclic [3,4,5,6,7], bicyclic [8] and acyclic guanidine alkaloids [9,10]. It is interesting that alkaloids produced in the sponges from different locations and depths had a variety of structures.…”
Section: Introductionmentioning
confidence: 99%
“…in 1989 by Kashman and co-workers. 11 In the following years, several PGA families, namely the crambescidins 12–15 , neofolitispates 16 , fromiamycalin 17 , celeromycalin 17 , monanchocidins 18,19 , monanchomycalins 20,21 and normonanchocidins 22 have been isolated, primarily from marine sponges and other aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%